Spirit Pribahasa Mambangkik Batang Tarandam In The Ceramic Artwork - Asmara, Dwita Anja (Institut Seni Indonesia Yogyakarta, 2022)
Mambangkik batang tarandam is a Minangkabau proverb meaning an attempt to revitalize something ancient to be beneficial and sustainable. There is a cultural transformation and value change in traditional art and lifestyle of the Minangkabau People. This creation aims at (1) understanding and internalizing the spirit of mambangkik batang tarandam contained in the forgotten, neglected, marginalized, and faded symbols through creative and innovative ceramic; (2) resurging the people, especially the people of Minangkabau, to revitalize Minangkabau’s traditional arts that have nearly been ignored and neglected. The art works were created in four phases: (1) Exploration; (2) Experiment; (3) Design; and (4) Realization. The ceramics were made of stoneware clay from Singkawang and Sukabumi. Pinching, slabbing, and casting techniques were employed. At the end, the ceramics were combined with bamboo, wood, cloth, and fiberglass as the supplementary materials. In conclusion, the created art works are expressed to do not only express beauty and self expression but become social criticism and awareness to maintain the presently neglected local wisdoms.